TI_GERICHTE 52.2018.261 vom 6. März 2018 , Revoca della licenza di condurre a tempo indeterminato. Effetto sospensivo - TI Tribunale d'appello (2018)
Revoca della licenza di condurre a tempo indeterminato. Effetto sospensivo